Pelatihan Media Tanam dan Propagasi Tanah pada Mahasiswa Pendidikan Biologi Universitas Pendidikan Mandalika - Harisanti, Baiq Muli; Fatmawati, Any; Armiani, Sucika; Hajiriah, Titi Laily; Marjan, Eyovin Payunang; Wahyuni, Heni (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
The objectives of this community service activity are: 1) to introduce and train the capabilities of students in the Department of Biology Education, Faculty of Science, Engineering, and Applied Sciences, Mandalika University of Education, on the correct method of mixing planting media; and 2) to teach students how to plant or propagate soil on Hypoestes plants. The community service activity was conducted within 1 day. The stages of this community service activity include: 1) introduction; 2) practical activities in making media and soil propagation; and 3) follow-up activities (observation for 1 week). Mixing planting media can influence the survival of the plants. Therefore, it requires appropriate and precise ratios to ensure that the mixture obtained can result in good plant growth. The soil propagation process in Hypoestes plants is also crucial for their ability to withstand external conditions and environmental shocks. By understanding these principles, students can enhance agricultural productivity, manage soil resources sustainably, and contribute to innovations in plant variety development.